Tomorrow We're All Going to the Harvest: Temporary Foreign Worker Programs and Neoliberal Political Economy - Binford, Leigh (University of Texas Press, 2013)
From its inception in 1966, the Canadian Seasonal Agricultural Worker Program (SAWP) has grown to employ approximately 20,000 workers annually, the majority from Mexico. The program has been hailed as a model that alleviates human rights concerns because, under contract, SAWP workers travel legally, receive health benefits, contribute to pensions, are represented by Canadian consular officials, and rate the program favorably. Tomorrow We?re All Going to the Harvest takes us behind the ideology and examines the daily lives of SAWP workers from Tlaxcala, Mexico (one of the leading sending states), observing the great personal and family price paid in order to experience a temporary rise in a standard of living. The book also observes the disparities of a gutted Mexican countryside versus the flourishing agriculture in Canada, where farm labor demand remains high. Drawn from extensive surveys and nearly two hundred interviews, ethnographic work in Ontario (destination of over 77 percent of migrants in the author?s sample), and quantitative data, this is much more than a case study; it situates the Tlaxcala-Canada exchange within the broader issues of migration, economics, and cultural currents. Bringing to light the historical genesis of ?complementary? labor markets and the contradictory positioning of Mexican government representatives, Leigh Binford also explores the language barriers and nonexistent worker networks in Canada, as well as the physical realities of the work itself, making this book a complete portrait of a provocative segment of migrant labor. --Publisher's description

Building More Effective Labour-Management Relationships - Chaykowski, Richard P.; Hickey, Robert Sean (Queen's policy studies series, 2013)
Building More Effective Labour-Management Relationships combines valuable insights into new approaches to relationship-building and collective bargaining with unique knowledge and concrete lessons garnered from some of the foremost industrial relations practitioners in Canada. Contributors include Warren "Smokey" Thomas (president, OPSEU), Buzz Hargrove (former president, CAW), Warren Edmondson (former ADM Labour, Government of Canada, and chair of the CLRB), George Smith (former VP at CP Rail and CBC/Radio Canada), David Logan, (ADM, Government of Ontario) Glenda Fisk (Queen's University), Richard Chaykowski (Queen's University), Robert Hickey (Queen's University). -- Publisher's description. Contents: Fostering Innovation and Cooperation in Employee Relations in the Ontario Public Service  / Warren "Smokey" Thomas -- An Introduction and Context Advancing Labour-Management Relationships and Cooperation / David Logan -- Systemic Pressures on Ontario Public Sector Industrial Relations / Richard P. Chaykowski, Robert S. Hickey --  Experiences in Collective Bargaining and the Labour-Management Relationship Remaking the Union-Management Relationship between the CBC and Canadian Media Guild: "We used to walk ... Now we talk" / Richard P. Chaykowski --  Reflections on Creating More Effective Labour Relations / George C.B. Smith Dan Oldfield -- Interest-Based, Cooperative Approaches to Negotiations and Labour Relations: What Works and What Does Not / Buzz Hargrove.
Keywords: Collective bargaining; Industrial relations

Clearing the Plains: Disease, Politics of Starvation, and the Loss of Aboriginal Life - Daschuk, James W. (James William) (University of Regina Press, 2013)
Revealing how Canada's first Prime Minister used a policy of starvation against Indigenous people to clear the way for settlement, the multiple award-winning Clearing the Plains sparked widespread debate about genocide in Canada. In arresting, but harrowing, prose, James Daschuk examines the roles that Old World diseases, climate, and, most disturbingly, Canadian politics-the politics of ethnocide-played in the deaths and subjugation of thousands of Indigenous people in the realization of Sir John A. Macdonald's "National Dream." It was a dream that came at great expense: the present disparity in health and economic well-being between Indigenous and non-Indigenous populations, and the lingering racism and misunderstanding that permeates the national consciousness to this day. --Publisher's description
Keywords: Indians of North America -- Canada, Western -- History

From Crisis to Austerity: Neoliberalism, Organized Labour and the Canadian State - Fowler, Tim (Red Quill Books, 2013)
The Great Recession was the largest crisis of capitalism since the Great Depression and the largest crisis in neoliberalism to date, sending shockwaves throughout the global economy. States scrambled to right the sinking capitalist ship in order to maintain high levels of accumulation. In Canada, as in so many other countries, the state introduced austerity measures aimed at organized labour and the broader working class. This volume explores the political economy of The Great Recession in Canada, and focuses on how labour has responded to the crisis, neoliberalism, and austerity measures. --Publisher's description. Contents: 1. From Crisis To Austerity: An Introduction / Tim Fowler -- 2. The Canadian State and the Crisis: Theoretical and Historical Context / Stephen McBride & Heather Whiteside -- 3. From the Great Recession of 2008-2009 to Fiscal Austerity: The Role of Inequality / Akhter Faroque and Brian K. MacLean  -- 4. Neoliberalism, Capitalist Crisis, and Continuing Austerity in the Ontario State / Tim Fowler  -- 5. Collective Bargaining in a Time of Austerity: Public-Sector Unions and the University Sector in Ontario / Mathew Nelson & James Meades --  6. "We Will Fight This Crisis": Auto Workers Resist an Industrial Meltdown/ Bill Murnighan & Jim Stanford -- 7. The Decline of the Labour Movement: A Socialist Perspective / Murray E.G. Smith & Jonah Butovsky -- 8. Labour’s Response to the Crisis and the Future of Working-Class Politics / David Camfield.

Provincial Solidarities: A History of the New Brunswick Federation of Labour - Frank, David (Working Canadians: Books from the CCLH, 2013)
Established in 1913, the New Brunswick Federation of Labour is the second oldest provincial federation of labour in Canada. Its history began in early campaigns for workers’ compensation and union recognition and continues today in the latest battles to defend social standards, secure employment, and union rights. Active initially in the port city of Saint John and the railway centre of Moncton, the federation soon expanded to include workers in the mines and mills of the north, taking up the causes of public employees and women workers and confronting the realities of life and work in a bilingual society. A pioneering study, written in clear and forceful prose, this is the untold story of provincial labour solidarities that succeeded in overcoming divisions and defeats to raise the status of working men and women within New Brunswick society. Drawing on archives, newspapers, and workers’ own descriptions of their experiences, Frank makes an original contribution to our understanding of the political, economic, and social development of the province. In so doing, he helps meet the need for an informed public awareness of the history of workers and unions in all parts of Canada.
Keywords: History; Labor Unions; Labor movement; New Brunswick Federation of Labour

Solidarités provinciales: Histoire de la Fédération des travailleurs et travailleuses du Nouveau-Brunswick - Frank, David; Comite canadien sur l'histoire du travail (Working Canadians: Books from the CCLH, 2013)
La Fédération des travailleurs et travailleuses du Nouveau-Brunswick, fondée en 1913, est la deuxième plus ancienne fédération provinciale du travail au Canada. Son histoire remonte aux premières campagnes en faveur de l’indemnisation des accidents du travail et de la reconnaissance syndicale, et elle se poursuit dans les plus récentes luttes visant à défendre les normes sociales et à protéger les emplois et les droits syndicaux. La Fédération a vu le jour dans la ville portuaire de Saint John et le centre ferroviaire de Moncton, puis elle s’est étendue aux travailleurs des mines et des usines du nord de la province, soutenant la cause des employés du secteur public et des travailleuses, reflétant les réalités de la vie et du travail dans une société bilingue. Puisant dans les archives, les journaux et les expériences des travailleurs et des travailleuses, voici l’histoire inédite de solidarités syndicales provinciales qui ont surmonté les divisions et les revers afin de rehausser le statut des travailleurs et des travailleuses dans la société néo-brunswickoise. Par cette étude pionnière rédigée dans un style clair et puissant, Frank apporte une contribution originale à la compréhension de l’évolution politique, économique et sociale de la province, et il aide à combler le besoin d’éclairer la connaissance que le public a de l’histoire des travailleurs et des syndicats de toutes les régions du Canada. --Publisher's description
Keywords: Histoire; Work

Producing and Negotiating Non-Citizenship: Precarious Legal Status in Canada - Goldring, Luin; Landolt, Patricia (University of Toronto Press, 2013)
This timely volume contributes to conceptualizing multiple forms of precarious status non-citizenship as connected through policy and the practices of migrants and the institutional actors they encounter. Most examinations of non-citizens in Canada focus on immigrants, people who are citizens-in-waiting, or specific categories of temporary, vulnerable workers. In contrast, Producing and Negotiating Non-Citizenship considers a range of people whose pathway to citizenship is uncertain or non-existent. This includes migrant workers, students, refugee claimants, and people with expired permits, all of whom have limited formal rights to employment, housing, education, and health services. The contributors to this volume present theoretically informed empirical studies of the regulatory, institutional, discursive, and practical terms under which precarious-status non-citizens – those without permanent residence – enter and remain in Canada. They consider the historical and contemporary production of non-citizen precarious status and migrant illegality in Canada, as well as everyday experiences of precarious status among various social groups including youth, denied refugee claimants, and agricultural workers. -- Publisher's description.
Keywords: Aliens; Canada; Congresses. Aliens; Congresses. Emigration and immigration law; Droit; Government policy. Emigration and immigration law. Rechtspositie. Allochtonen. Auslnderpolitik Auslnderrecht Illegaler Einwanderer Genre/Form: Conference papers and proceedings; Social conditions; Social conditions. Emigration and immigration

Now You're Logging - Griffiths, Bus; Hodgins, Jack (Harbour Publishing, 2013)
This comic was originally produced for B.C. Lumbermen. It first appeared in a war-time comic strip. Whether readers are interested in logging history, a good yarn or folk art, they will be enthralled by Now You're Logging, British Columbia's first graphic novel and a enduring West Coast classic, published in celebration of what would have been Bus Griffiths' 100th birthday. Now You're Logging is the story of Al and Red, who go to work in a small West Coast logging show during the dirty thirties. As they learn their trades, the reader is treated to an amazingly detailed view of the camp's varied operations—falling and bucking timber by hand, topping and rigging of spar trees, moving steam donkeys and making up log booms, plus all the colourful characters, camaraderie, romance and life-threatening exploits of a BC adventure story. --Publisher's description
Keywords: Adventure; Agriculture, Forestry, Fishing and Hunting; Logging; Working class

The Left in British Columbia: A History of Struggle - Hak, Gordon H. (Gordon Hugh) (Ronsdale Press, 2013)
This comprehensive history of the left in British Columbia from the late nineteenth century to the present explores the successes and failures of individuals and organizations striving to make a better world. Nineteenth-century coal miners and carpenters; Wobblies, Single Taxers, and communists; worker militancy in two world wars; the New Democratic Party; the Squamish Five; the Solidarity movement of 1983; and the Occupy movement of 2011 are all part of an historical provincial left that is notable for its breadth and dynamism. Moreover, the political and union initiatives of the traditional left are seen in conjunction with broader movements, including the struggles for women's suffrage and equality, human rights, Canadian nationalist visions, racial equality, and environmental health. Ginger Goodwin and Dave Barrett (as well as WAC Bennett and Gordon Campbell) are present, as are reformist liberals and green activists. Drawing on extensive published scholarship and primary newspaper sources, Dr. Hak's thorough examination of the British Columbia experience offers an historical context for understanding the contemporary left and a framework for considering future alternatives.

Hazard or Hardship: Crafting Global Norms on the Right to Refuse Unsafe Work - Hilgert, Jeffrey (Cornell University Press, 2013)
Today, hazardous work kills 2.3 million people each year and injures millions more. Among the most compelling yet controversial forms of legal protection for workers is the right to refuse unsafe work. The rise of globalization, precarious work, neoliberal politics, attacks on unions, and the idea of individual employment rights have challenged the protection of occupational health and safety for workers worldwide. This book presents the protection of refusal rights as a moral and a human rights question. The book finds that the protection of the right to refuse unsafe work, as constituted under international labor standards, is a failure and calls for a reexamination of worker health and safety policy from the ground up. The current model of protection follows an individual employment rights framework, which fails to protect workers against the inherent social inequalities within the employment relationship. To adequately protect the right to refuse as a human right, both in North America and around the world, the book argues that a broader protection must be granted under a freedom of association framework.

Feminist History in Canada: New Essays on Women, Gender, Work, and Nation - Janoviček, Nancy; Carstairs, Catherine (UBC Press, 2013)
In the late 1970s, feminist historians urged us to “rethink” Canada by placing women’s perspectives and experiences at the centre of historical analysis. Forty years later, feminism continues to inform history writing in Canada and has inspired historians to look beyond the nation and adopt a more global perspective. This exciting new volume of original essays opens with a discussion of the debates, themes, and methodological approaches that have preoccupied women’s and gender historians across Canada over the past twenty years. The chapters that follow showcase the work of new and established scholars who draw on the insights of critical race theory, postcolonial theory, and transnational history to re-examine familiar topics such as biography and oral history, paid and unpaid work, marriage and family, and women’s political action. Whether they focus on the marriage of Governor James Douglas and his Metis wife, Amelia; representations of saleswomen in department store catalogues; or the careers of professional women such as international child activist Charlotte Whitton and Quebec social work professors at Laval University, the contributors demonstrate the continued relevance – and growth – of history informed by feminist perspectives, and they open a much-needed dialogue between francophone and anglophone historians in Canada.-- Publisher's description
Keywords: Aufsatzsammlung; Biographies; Canada; Feminism; Feminism Canada History; Feminismus; Femmes Canada Biographies; Femmes Canada Conditions sociales; Femmes Canada Histoire; Frau; Frauenbewegung; Féminisme Canada Histoire; Geschlechterrolle; History; Kanada; Women; Women Canada Biography; Women Canada History; Women Canada Social conditions; Women Social conditions

Fernand Daoust - Leclerc, André (Collection Militantismes, 2013)
Fernand Daoust est surtout connu pour avoir été un dirigeant central de la Fédération des travailleurs et travailleuses du Québec (FTQ) pendant vingt-quatre ans. Or, cela est le fruit d'un véritable parcours du combattant dans le mouvement ouvrier. Le syndicaliste est né en 1926 dans des conditions très modestes et élevé dans une famille monoparentale. Sa curiosité, sa soif de connaissance et sa détermination l'ont entraîné bien au-delà des activités auxquelles ses origines le destinaient. Dans cette première partie de sa biographie, qui couvre les années 1926-1964, nous l'accompagnons dans le Montréal de la grande dépression, nous assistons à ses premiers engagements nationalistes pendant la crise de la conscription, à sa découverte des idéologies progressistes et à son entrée dans le mouvement syndical, malgré les dures conditions imposées aux syndicalistes par le régime Duplessis. Nous le voyons découvrir la nécessité de l'action politique et pressentons le futur dirigeant syndical. Accédant aux études universitaires à force de courage et de persévérance, son horizon intellectuel s'élargit. C'est tout naturellement qu'il choisit le syndicalisme pour y développer et approfondir son engagement social et politique. En faisant sienne l'idéologie socialiste, qui inspire les courants les plus dynamiques du syndicalisme québécois, le jeune syndicaliste ne renie cependant pas ses racines. Son socialisme s'incarne dans une nation spécifique, celle du Québec. Il n'était pas d'accord avec une majorité de syndicalistes de gauche de l'époque, qui qualifiaient de rétrogrades les aspirations nationales québécoises. Au contact des idées de gauche, le nationalisme de droite, dans lequel il avait baigné à l'adolescence et auquel il n'avait jamais totalement adhéré, a fait place à un nationalisme progressiste, précurseur de celui qu'allait épouser une proportion grandissante de la population québécoise.
Keywords: 20e siècle; 20th century; Daoust, Fernand, 1926-; Dirigeants syndicaux; Fédération des travailleurs et travailleuses du Québec; Histoire; History; Labor leaders; Quebec Federation of Labour; Québec (Province); Syndicalism; Syndicalisme

Rebel Life: The Life and Times of Robert Gosden, Revolutionary, Mystic, Labour Spy - Leier, Mark (James Mark) (New Star Books, 2013)
Extensively revised throughout and including a chapter of new material, Rebel Life chronicles the life of labour organizer, revolutionary, anarchist and labour spy Robert Gosden. Mark Leier's revisions incorporate new information about Gosden's career that has come to light since the first edition was published in 1999. Canada's west coast was rife with upheaval in the second and third decades of the twentieth century. At the centre of the turmoil is Robert Gosden, migrant labourer turned radical activistヨturned police spy. In 1913, he publicly recommends assassinating Premier Richard McBride to resolve theminers' strike. By 1919, he is urging Prime Minister Robert Borden to "disappear" key labour radicals to quelch rising discontent. What happened?Rebel Life plumbs the enigma that was Gosden, but it is much more: an introduction to BC labour history: a trove of rarely seen archival photograph, and sidebars rich with historical arcana; and, with its chapter describing the research that unearthed Gosden's story, Rebel Life is a rich resource for instructors, students, and trade unionists alike.

Climate@Work - Lipsig-Mummé, Carla (Labour in Canada (Halifax, N.S.), 2013)
Climate change is having an increasingly significant impact on work in Canada, and the effect climate change has, and will continue to have, on work concerns many Canadians. However, this fact has not been seriously considered either in academic circles, in the labour movement nor especially by the Canadian government. Climate@Work addresses this deficit by systematically tackling the question of the impact of climate change on work and employment and by analyzing Canada’s conservative silence towards climate change and the Canadian government’s refusal to take it seriously.--Publisher's description. Contents: Introduction. Section 1: Contexts.Changing Patterns in the Literature of Climate Change and Canadian Work: The Research of Academics, Government and Social Actors / Elizabeth Perry -- Climate, Work and Labour: the International Context / Carla Lipsig-Mummé --International Trade Agreements and the Ontario Green Energy Act: Opportunities and Obstacles / Stephen McBride & John Shields. Section 2: Sectors. The Impact of Climate Change on Employment and Skills Requirements in the Construction Industry / John O’Grady -- Climate Change and Labour in the Energy Sector / Marjorie Griffin Cohen & John Calvert -- The Transportation Equipment Industry / John Holmes, with Austin Hracs -- The Forestry Industry / John Holmes -- Tourism, Climate Change and the Missing Worker: Uneven Impacts, Institutions and Response / Steven Tufts -- Climate Change and Work and Employment in the Canadian Postal and Courier Sector / Meg Gingrich, Sarah Ryan & Geoff Bickerton. Includes bibliographical references (pages 177-196).
Keywords: Canada. Climatic changes; Climatic changes; Economic aspects; Economic aspects. Climatic changes; Government policy

From Demonized to Organized: Building the New Union Movement - Loreto, Nora (Our schools, our selves book series, 2013)
This book seeks to explain unionization to my generation; to my friends who distrust civil society organizations as much as they distrust government; to my unemployed friends who are living from contract to contract and who would kill for a stable, unionized job; for the workers who have never had the benefit of being represented when facing injustice at work; for the workers who would rather not think of what would happen if they were injured on the job. It’s a reminder to unionized folks that many of the truths that they take for granted are not obvious to others and that the labour movement must change how it reaches out to its members, its communities and to non-unionized workers if it hopes to grow. It’s a call to action for activists to share their stories, debunk the existing right-wing, anti-union rhetoric, re-engage in their communities, and build a movement that can defeat neoliberal policies and their political proponents. --From author's introduction
Keywords: Labour unions

Indigenous Women, Work, and History, 1940-1980 - McCallum, Mary Jane (Critical studies in Native history ; 16, 2013)
When dealing with Indigenous women’s history we are conditioned to think about women as private-sphere figures, circumscribed by the home, the reserve, and the community. Moreover, in many ways Indigenous men and women have been cast in static, pre-modern, and one-dimensional identities, and their twentieth century experiences reduced to a singular story of decline and loss. In Indigenous Women, Work, and History, historian Mary Jane Logan McCallum rejects both of these long-standing conventions by presenting case studies of Indigenous domestic servants, hairdressers, community health representatives, and nurses working in “modern Native ways” between 1940 and 1980. Based on a range of sources including the records of the Departments of Indian Affairs and National Health and Welfare, interviews, and print and audio-visual media, McCallum shows how state-run education and placement programs were part of Canada’s larger vision of assimilation and extinguishment of treaty obligations. Conversely, she also shows how Indigenous women link these same programs to their social and cultural responsibilities of community building and state resistance. By placing the history of these modern workers within a broader historical context of Aboriginal education and health, federal labour programs, post-war Aboriginal economic and political developments, and Aboriginal professional organizations, McCallum challenges us to think about Indigenous women’s history in entirely new ways. --Publisher's description. Contents: Sweeping the Nation: Indigenous women and domestic labour in mid-twentieth-century Canada -- Permanent solution: the placement and relocation program, hairdressers, and beauty culture -- Early labour history of community health representatives, 1960-1970 -- Gaining recognition: labour as activism among Indigenous nurses -- Wages of whiteness and the Indigenous historian.
Keywords: 20th century; Economic conditions; Employment; History; Indigenous women; Social conditions

Dominion of Capital: The Politics of Big Business and the Crisis of the Canadian Bourgeoisie, 1914-1947 - Nerbas, Don (University of Toronto Press, 2013)
In the critical decades following the First World War, the Canadian political landscape was shifting in ways that significantly recast the relationship between big business and government. As public pressures changed the priorities of Canada's political parties, many of Canada's most powerful businessmen struggled to come to terms with a changing world that was less sympathetic to their ideas and interests than before. Dominion of Capital offers a new account of relations between government and business in Canada during a period of transition between the established expectations of the National Policy and the uncertain future of the twentieth century. Don Nerbas tells this fascinating story through close portraits of influential business and political figures of this period - including Howard P. Robinson, Charles Dunning, Sir Edward Beatty, R.S. McLaughlin, and C.D. Howe - that provide insight into how events in different sectors of the economy and regions of the country shaped the political outlook and strategies of the country's business elite. Drawing on business, political, social, and cultural history, Nerbas revises standard accounts of government-business relations in this period and sheds new light on the challenges facing big business in early twentieth-century Canada. --Publisher's description. Contents: Part 1: Big Business from Triumph to Crisis. Provincial Man of Mystery: Howard P. Robinson and the Politics of Capital in New Brunswick -- Charles A. Dunning: A Progressive in Business and Politics -- The Dilemma of Democracy: Sir Edward Beatty, the Railway Question, and National Government. Part 2: Continentalism and the Managerial Ethic. -- Stewardship and Dependency: Sam McLaughlin, General Motors, and the Labour Question -- Engineering Canada: C.D. Howe and Canadian Big Business -- Conclusion -- Après le déluge -- Endnotes.

Public Sector Unions in the Age of Austerity - Ross, Stephanie; Savage, Larry (Labour in Canada (Halifax, N.S.), 2013)
For decades, public sector unions in Canada have been plagued by austerity, privatization, taxpayer backlash and restrictions on union rights. In recent years, the intensity of state-led attacks against public sector workers has reached a fevered pitch, raising the question of the role of public sector unions in protecting their members and the broader public interest. Public Sector Unions in the Age of Austerity examines the unique characteristics of public sector unionism in a Canadian context. Contributors to this multi-disciplinary collection explore both the strategic possibilities and challenges facing public sector unions that are intent on resisting austerity, enhancing their power and connecting their interests as workers with those of citizens who desire a more just and equitable public sphere. --Publisher's description

Rethinking Workplace Regulation: Beyond the Standard Contract of Employment - Stone, Katherine Van Wezel; Arthur, Harry W. (Russell Sage Foundation, 2013)
During the middle third of the 20th century, workers in most industrialized countries secured a substantial measure of job security, whether through legislation, contract or social practice. This "standard employment contract," as it was known, became the foundation of an impressive array of rights and entitlements, including social insurance and pensions, protection against unsociable working conditions, and the right to bargain collectively. Recent changes in technology and the global economy, however, have dramatically eroded this traditional form of employment. Employers now value flexibility over stability, and increasingly hire employees for short-term or temporary work. Many countries have also repealed labor laws, relaxed employee protections, and reduced state-provided benefits. As the old system of worker protection declines, how can labor regulation be improved to protect workers? In Rethinking Workplace Regulation, nineteen leading scholars from ten countries and half a dozen disciplines present a sweeping tour of the latest policy experiments across the world that attempt to balance worker security and the new flexible employment paradigm. Edited by noted socio-legal scholars Katherine V.W. Stone and Harry Arthurs, Rethinking Workplace Regulation presents case studies on new forms of dispute resolution, job training programs, social insurance and collective representation that could serve as policy models in the contemporary industrialized world. The volume leads with an intriguing set of essays on legal attempts to update the employment contract. For example, Bruno Caruso reports on efforts in the European Union to "constitutionalize" employment and other contracts to better preserve protective principles for workers and to extend their legal impact. The volume then turns to the field of labor relations, where promising regulatory strategies have emerged. Sociologist Jelle Visser offers a fresh assessment of the Dutch version of the 'flexicurity' model, which attempts to balance the rise in nonstandard employment with improved social protection by indexing the minimum wage and strengthening rights of access to health insurance, pensions, and training. Sociologist Ida Regalia provides an engaging account of experimental local and regional "pacts" in Italy and France that allow several employers to share temporary workers, thereby providing workers job security within the group rather than with an individual firm. The volume also illustrates the power of governments to influence labor market institutions. Legal scholars John Howe and Michael Rawling discuss Australiaʹs innovative legislation on supply chains that holds companies at the top of the supply chain responsible for employment law violations of their subcontractors. Contributors also analyze ways in which more general social policy is being renegotiated in light of the changing nature of work. Kendra Strauss, a geographer, offers a wide-ranging comparative analysis of pension systems and calls for a new model that offers "flexible pensions for flexible workers. With its ambitious scope and broad inquiry, Rethinking Workplace Regulation illustrates the diverse innovations countries have developed to confront the policy challenges created by the changing nature of work. The experiments evaluated in this volume will provide inspiration and instruction for policymakers and advocates seeking to improve worker's lives in this latest era of global capitalism. --Publisherʹs description
Keywords: Arbetsavtal; Arbetsmarknad; BUSINESS & ECONOMICS Labor; Contrat de travail; Labor contract; Osgoodiana

The Wages of Relief: Cities and the Unemployed in Prairie Canada, 1929-39 - Strikwerda, Eric (Working Canadians: Books from the CCLH, 2013)
In the early part of the Dirty Thirties, the Canadian prairie city was a relatively safe haven. Having faced recession before the Great War and then again in the early 1920s, municipalities already had relief apparatuses in place to deal with poverty and unemployment. Until 1933, responsibilty for the care of the urban poor remained with local governments, but when the farms failed that year, and the Depression deepened, western Canadian cities suffered tremendously. Recognizing the severity of the crisis, the national government intervened. Evolving federal programs and policies took over responsibility for the delivery of relief to the single unemployed, while the government simultaneously withdrew financing for all public works projects. Setting municipal relief administrations of the 1930s within a wider literature on welfare and urban poor relief, Strikwerda highlights the legacy on which relief policymakers relied in determining policy directions, as well as the experiences of the individuals and families who depended on relief for their survival. Focusing on three prairie cities—Edmonton, Saskatoon, and Winnipeg—Strikwerda argues that municipal officials used their power to set policy to address what they perceived to be the most serious threats to the social order stemming from the economic crisis. By analyzing the differing ways in which local relief programs treated married and single men, he also explores important gendered dynamics at work in the response of city administrators to the social and economic upheaval of the Depression. Probing the mindset of local elites struggling in extraordinary circumstances, The Wages of Relief describes the enduring impact of the policy changes made in the 1930s in the direction of a broad, national approach to unemployment—an approach that ushered in Canada’s modern welfare system. --Publisher's description
Keywords: 1905-1945; 20th century; Cities and towns; Economic conditions; Government policy History; History; MUNICIPAL government; Prairie Provinces; Public welfare administration; Social aspects History; Social conditions; Unemployed; Urban economics

Manufacturing Mennonites: Work and Religion in Post-War Manitoba - Thiessen, Janis Lee (Canadian social history series, 2013)
Manufacturing Mennonites examines the efforts of Mennonite intellectuals and business leaders to redefine the group's ethno-religious identity in response to changing economic and social conditions after 1945. As the industrial workplace was one of the most significant venues in which competing identity claims were contested during this period, Janis Thiessen explores how Mennonite workers responded to such redefinitions and how they affected class relations. Through unprecedented access to extensive private company records, Thiessen provides an innovative comparison of three businesses founded, owned, and originally staffed by Mennonites: the printing firm Friesens Corporation, the window manufacturer Loewen, and the furniture manufacturer Palliser. Complemented with interviews with workers, managers, and business owners, Manufacturing Mennonites pioneers two important new trajectories for scholarship - how religion can affect business history, and how class relations have influenced religious history. --Publisher's description

Joe Salsberg: A Life of Commitment - Tulchinsky, Gerald J. J. (University of Toronto Press, 2013)
This book follows the life and intellectual journey of Joseph Baruch Salsberg, a Polish-Jewish immigrant who became a major figure of the Ontario Left, a leading voice for human rights in the Ontario legislature, and an important journalist in the Jewish community. His life trajectory mirrored many of the most significant transformations in Canadian political and social life in the twentieth century. Award-winning historian Gerald Tulchinsky traces Salsberg’s personal and professional journey – from his entrance into Toronto’s oppressive garment industry at age 14, which led to his becoming active in emerging trade unions, to his rise through the ranks of the Communist Party of Canada and the Workers’ Unity League. Detailing Salsberg’s time as an influential Toronto alderman and member of the Ontario legislature, the book also examines his dramatic break with communism and his embrace of a new career in journalism. Tulchinsky employs historical sources not used before to explain how Salsberg’s family life and surrounding religious and social milieu influenced his evolution as a Zionist, an important labour union leader, a member of the Communist Party of Canada, and a prominent member of Toronto’s Jewish community. --Publisher's description
Keywords: Communists; Jews; Labor union members; Politicians; Politics and government; Salsberg, J. B. (Joseph B.), ca. 1903-1998; Social conditions

Selling Sex: Experience, Advocacy, and Research on Sex Work in Canada - Van der Meulen, Emily; Durisin, Elya M.; Love, Victoria (Sexuality studies series, 2013)
Despite being dubbed "the world's oldest profession," prostitution has rarely been viewed as a legitimate form of labour. Instead, it has been criminalized, sensationalized, and polemicized across the socio-political spectrum by everyone from politicians to journalists to women's groups. Interest in and concern over sex work is not grounded in the lived realities of those who work in the industry, but rather in inflammatory ideas about who is participating, how they wound up in this line of work, and what form it takes. In Selling Sex, Emily van der Meulen, Elya M. Durisin, and Victoria Love present a more nuanced, balanced, and realistic view of the sex industry. They bring together a vast collection of voices - including researchers, feminists, academics, and advocates, as well as sex workers of differing ages, genders, and sectors - to engage in a dialogue that challenges the dominant narratives surrounding the sex industry and advances the idea that sex work is in fact work. Presenting a variety of opinions and perspectives on such diverse topics as the social stigma of sex work, police violence, labour organizing, anti-prostitution feminism, human trafficking, and harm reduction, Selling Sex is an eye-opening, challenging, and necessary book. --Publisher's description
Keywords: Government policy; Labor Unions; Law and legislation; Organizing; Prostitutes; Prostitution; Sex-oriented businesses

Du pain ou du sang : les travailleurs irlandais et le canal de Beauharnois - Viau, Roland (PUM, 2013)
Le 12 juin 1843 restera dans la mémoire comme le « Lundi rouge » : un jour funeste, où plusieurs ouvriers irlandais affectés au creusement du canal Beauharnois trouvent la mort pour avoir réclamé de meilleures conditions de travail. Plus de deux mille « canaliers » en grève illégale subissent la charge des troupes de la garnison qui les dispersent avec une violence démesurée devant l’hôtel où logent leurs patrons – feux, sabres et chevaux contre pelles, pioches et gourdins. Cet événement tragique marque à ce jour le conflit de travail le plus sanglant de l’histoire du Canada. L’indignation générale contraint le gouvernement à instituer une des premières enquêtes publiques du pays. Une enquête biaisée, comme le démontre brillamment Roland Viau qui examine de nouvelles pièces au dossier en faisant revivre le quotidien des familles irlandaises installées le long du canal. Il aboutit à des constats troublants, révélant l’arbitraire des tribunaux envers ces travailleurs migrants honteusement exploités et méprisés, et met à jour l’existence d’une société secrète qui préfigure le mouvement syndical. --Publisher's description
Keywords: 1800-1899; Beauharnois Canal (Québec) History 19th century; Beauharnois Canal Strike, Québec, 1843; Canal de Beauharnois (Québec) Histoire 19e siècle; Canals Design and construction; Canals Québec (Province) Beauharnois Design and construction History; Canaux Québec (Canada; province) Beauharnois (Canada) Conception et construction; Canaux Québec (Province) Beauharnois Conception et construction Histoire; Condition sociale; Condition économique; Foreign workers, Irish Québec (Province) Economic conditions 19th century; Foreign workers, Irish Québec (Province) Social conditions 19th century; Grève des ouvriers du canal de Beauharnois (Québec, 1843); Grève des ouvriers du canal de Beauharnois, Québec, 1843; History; Irlandais; Québec; Québec Beauharnois; Québec Beauharnois Canal; Travailleur étranger; Travailleurs étrangers irlandais Québec (Canada; province) Conditions rurales 19e siècle; Travailleurs étrangers irlandais Québec (Canada; province) Conditions rurales Conditions économiques 19e siècle; Travailleurs étrangers irlandais Québec (Province) Conditions sociales 19e siècle; Travailleurs étrangers irlandais Québec (Province) Conditions économiques 19e siècle